Moisture curable compositions and adhesives containing the same

By adding silylated acrylate and an amine-based catalyst to the moisture-curable polyoxyalkylene polymer, the problem of the moisture-curable composition losing water resistance in water in the prior art is solved, and a cured product with high water resistance and rubber properties is achieved.

CN119866359APending Publication Date: 2025-04-22WACKER CHEMIE AG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380065787.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-16
Filing Date
2023-09-06
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

The existing moisture curable compositions are difficult to maintain excellent water resistance and rubber properties after immersion in water, especially tensile bonding strength.

Method used

By adding a specific silylated acrylate to a moisture-curable polyoxyalkylene polymer with a crosslinkable silyl group at the end, and using an amine-based catalyst with an alkoxy group, a cured product with high water resistance and rubber properties is formed.

Benefits of technology

The composition that cures by moisture in the air at room temperature has good rubber properties and excellent water resistance, including good tensile bonding strength, which can be maintained even after immersion in water.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005309650830000291
    Figure BDA0005309650830000291
  • Figure BDA0005309650830000301
    Figure BDA0005309650830000301
Patent Text Reader

Abstract

The present invention provides a moisture curable composition in which a metal catalyst is not used in consideration of environmental and safety, and which forms a cured product having high water-resistant adhesion and rubber properties, including physical properties of good tensile strength and elongation. A moisture-curable composition comprising a silane-modified polymer having the group Y-[CH2-SiR1a (OR2) 3-a] is mixed with a (meth) acrylate polymer containing a crosslinkable silyl group in the molecule and an amine-based catalyst having at least one alkoxy group.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a moisture-curable composition, and more particularly, to a moisture-curable composition that can be cured at room temperature by moisture in the air, etc. to form a cured product having good rubber properties and exhibiting excellent water-resistant adhesion including good tensile adhesive strength even after being immersed in water. Background Art

[0002] It is known that an organic polymer having a crosslinkable silyl group is crosslinked through a siloxane bond formed by moisture or the like even at room temperature under a hydrolysis reaction of the crosslinkable silyl group to form a rubber cured product. Among these polymers, polyoxyalkylene-based polymers having a crosslinkable silyl group are widely used as adhesives, sealing materials or coatings for construction applications, applications involving electrical and electronic fields, and applications involving automotive fields.

[0003] By selecting various components, such as fillers and plasticizers, to blend a curable composition including an organic polymer containing a crosslinkable silyl group, various physical properties can be adjusted.

[0004] For example, Patent Document 1 discloses a modified silicone-based resin composition having improved water-resistant adhesion obtained by adding a curable composition containing a polymer (B) having an alkyl acrylate monomer unit and / or an alkyl methacrylate monomer unit as a molecular chain to a polyoxyalkylene-based polymer having a silicon-containing functional group.

[0005] Use hydrolysis catalyst to solidify curable composition.As catalyst, usually use organotin catalyst, such as dibutyltin dilaurate.But organotin catalyst is poisonous, therefore consider environment and personal safety, need wherein organotin compound is not used for the moisture curable composition of solidification.The adhesive property (tensile bond strength) after the obtained solidified product is immersed in water needs further improvement.

[0006] Patent Document 2 discloses a moisture-curable composition containing a silane crosslinkable polymer and at least one reaction product prepared from at least one aminosilane having at least one primary amino group and an olefin having no silane group capable of 1,4-addition reaction with the primary amino group, the composition having excellent water-resistant adhesion based on evaluation of cohesive fracture. However, Patent Document 2 does not mention the tensile adhesive strength after immersion in water, and it is unclear whether sufficient adhesive properties are maintained after immersion in water.

[0007] For compositions mainly containing silane-crosslinkable polymers, compositions showing sufficient water-resistant adhesion are unknown.

[0008] Reference List

[0009] Patent Literature

[0010] Patent Document 1: Japanese Patent Application Publication No. 2003-313419

[0011] Patent Document 2: WO2007 / 085622 (Japanese translation of PCT Patent Application Publication No. 2009-524721) Summary of the invention

[0012] Technical issues

[0013] As mentioned above, a moisture curable composition has not been found that can form a cured product having excellent water-resistant adhesion (including good tensile bond strength) even after immersion in water. In addition, a cured product showing excellent rubber properties (including high tensile strength and elongation) is desired.

[0014] An object of the present invention is to provide a moisture curable composition in which no metal catalyst is used in consideration of environment and safety, and which forms a cured product having high water-resistant adhesion and rubber properties including good physical properties of tensile strength and elongation.

[0015] Solutions to the problem

[0016] The present inventors have found that the above-mentioned problems can be solved by adding a specific silylated acrylate to a moisture-curable polyoxyalkylene polymer having a crosslinkable silyl group at the terminal, thereby completing the present invention.

[0017] Specifically, the present invention is a moisture curable composition comprising:

[0018] Component (A) which is a silane-modified polymer represented by the general formula (1):

[0019] Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0020] (wherein Y is an x-valent polymer group bonded via nitrogen, oxygen or sulfur,

[0021] R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups, R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group,

[0022] x is an integer from 1 to 10, and;

[0023] a is 0, 1, or 2);

[0024] Component (B) which is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule (ie, a polymer of an ester of (meth)acrylic acid); and

[0025] Component (C) which is an amine-based catalyst having at least one alkoxy group.

[0026] The above moisture curable composition can be cured without a metal catalyst represented by an organic tin catalyst and exhibits good adhesion to a substrate. The moisture curable composition containing components (B) and (C) can exhibit good adhesion even after being immersed in water.

[0027] The present invention is a method comprising including component (B) in a moisture-curable composition comprising the above-mentioned components (A) and (C) so that the tensile adhesive strength of the cured product to a substrate after being subjected to a water immersion test is equal to or greater than the tensile adhesive strength before being subjected to the water immersion test, in which they are immersed in water at 23° C. for 168 hours.

[0028] After bonding the substrate by applying the moisture curable composition to the substrate and curing the moisture curable composition, when the cured product is contacted with water, the bond strength of the cured product to the substrate generally tends to decrease. However, the present invention allows the bond strength after contact with water to be maintained or the bond strength to be improved.

[0029] The moisture curable composition of the present invention may include at least one liquid component product. The moisture curable composition may have any aspect or form, as long as the cured product of the moisture curable composition is ultimately obtained by curing with moisture. In the presence of an amine-based catalyst (component (C)) having an alkoxy group, the moisture curable composition containing the -CH2-SiR 1 a (OR 2 ) 3-a The polyoxyalkylene polymer (component (A)) having an alkoxysilane represented as a terminal group is hydrolyzed to generate silanol. By the dehydration-condensation reaction of the silanol, a matrix is ​​formed through a siloxane bond to cure the moisture curable composition.

[0030] The (meth)acrylate polymer having a crosslinkable silyl group in the molecule (component (B)) is incorporated into the matrix due to the crosslinkable silyl group in the component (B), which contributes to improved water-resistant adhesion.

[0031] Since component (A) has a crosslinkable silyl group at the α position of the polymer chain, component (A) is highly reactive, and the moisture curable composition can be cured by crosslinking reaction in the absence of a metal catalyst represented by an organotin catalyst. Specifically, the crosslinking reaction of component (A) is carried out due to water (such as moisture in air) in the presence of an amine-based catalyst as component (C), and the moisture curable composition is cured. The cured product of the moisture curable composition containing component (A) exhibits high rubber properties (high tensile strength and high elongation). When a (methyl) acrylate polymer (B) with a crosslinkable silyl group is added, a matrix is ​​formed with component (A) by crosslinking reaction. Therefore, while maintaining the elongation of the cured product, the tensile strength of the cured product can be improved.

[0032] By interacting with the substrate, the ester group in component (B) plays the role of bonding the cured moisture curable composition to the substrate. Therefore, compared with the substrate formed by only crosslinking of component (A), the substrate containing component (B) is more firmly bonded to the substrate. Even when the cured product is exposed to water (that is, after being immersed in water), the phenomenon of reducing tensile bond strength due to water entering the space between the substrate and the cured product can also be suppressed. Since component (B) is a polymer with a methyl group in the main chain, the rotation of the main chain is restricted compared with the situation that the polymer does not have a methyl group. Therefore, the crystallinity is high. Therefore, water can be suppressed from entering from the outside.

[0033] The alkoxy moiety in the molecule of component (C) binds to components (A) and (B), so that component (C) is incorporated into the matrix. Due to the interaction of the amino moiety with the substrate, the adhesion of the cured product to the substrate is further improved.

[0034] Since component (B) has a silyl group, component (B) has good compatibility with component (A), and the uniform chemical composition of the moisture-curable composition can be maintained for a long time. Therefore, the moisture-curable composition of the present invention has excellent storage stability.

[0035] The moisture-curable composition of the present invention is suitable as an adhesive, a sealant or a coating material. In particular, the moisture-curable composition having excellent water-resistant adhesion is used as an adhesive or a sealant for bonding substrates. DETAILED DESCRIPTION

[0036] The present invention is described in detail below.

[0037] The moisture curable composition of the present invention comprises:

[0038] Component (A) which is a silane-modified polymer represented by the general formula (1):

[0039] Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0040] (wherein Y is an x-valent polymer group bonded via nitrogen, oxygen or sulfur,

[0041] R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups,

[0042] R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group,

[0043] x is an integer from 1 to 10, and;

[0044] a is 0, 1, or 2);

[0045] Component (B) which is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule (ie, a (meth)acrylate polymer); and

[0046] Component (C) which is an amine-based catalyst having at least one alkoxy group.

[0047] In the above formula (1), Y has a polymer chain which is a polyoxyalkylene and is connected to -OC(=O)-NH- or -NH-C(=O)-NR'- via -[CH2-SiR 1 a (OR 2 ) 3-a ] group bonded to the group, R 1 may be the same as or different from each other and are monovalent optionally substituted silicon-bonded hydrocarbon groups, R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group, R′ is a monovalent optionally substituted silicon-bonded hydrocarbon group, and a may be 0, 1 or 2.

[0048] The above-mentioned moisture-curable composition may be a composition containing 5 parts by mass or more and 90 parts by mass or less of component (A), 5 parts by mass or more and 90 parts by mass or less of component (B), and 0.01 parts by mass or more and 10 parts by mass or less of component (C), relative to 100 parts by mass of the entire moisture-curable composition.

[0049] Component A:

[0050] The silane-modified polymer (A) in the present invention contains at least one alkoxysilyl group defined in the polymer represented by the above general formula (1). The group may be an alkoxysilyl group bonded to one end of the polymer backbone. Component (A) is preferably a silane-modified polymer comprising at least one polyoxyalkylene structural unit.

[0051] The silane-modified polymer (A) as the main component of the moisture-curable composition is capable of forming a cured product by moisture after application.

[0052] The silane-modified polymer (A) can be purchased as a commercial product, and can also be produced by a common chemical method. The silane-modified polymer (A) can be used alone, or a mixture of two or more types thereof can be used in combination.

[0053] The silane-modified polymer (A) can be a so-called α-silane-terminated polymer having a crosslinkable alkoxysilyl group bonded to adjacent urethane units via a methylene spacer. Since the silane-modified polymer (A) with such a structure achieves a high curing rate when it is in contact with air, the silane-modified polymer (A) has high safety in that no toxic tin catalyst is required and has a low environmental load. Examples of commercially available α-silane-terminated polymers include GENIOSIL (registered trademark) STP-E 10 and STP-E 30, available from Wacker Chemie AG.

[0054] Group R 1 It is a monovalent optionally substituted hydrocarbon group bonded to SiC.

[0055] Group R 1 Examples of include alkyl groups such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, tert-pentyl, hexyl groups such as n-hexyl, heptyl groups such as n-heptyl, octyl groups such as n-octyl, isooctyl and 2,2,4-trimethylpentyl, nonyl groups such as n-nonyl, decyl groups such as n-decyl, dodecyl groups such as n-dodecyl, and octadecyl groups such as n-octadecyl; cycloalkyl groups such as cyclopentyl groups, cyclohexyl groups, cycloheptyl groups and methylcyclohexyl groups; alkenyl groups such as vinyl, 1-propenyl and 2-propenyl; aryl groups such as phenyl groups, naphthyl groups, anthracenyl groups and phenanthrenyl groups; alkylaryl groups such as o-tolyl, m-tolyl and p-tolyl, xylyl and ethylphenyl; and aralkyl groups such as benzyl, α- and β-phenylethyl groups.

[0056] Substituent R 1Examples include halogenated alkyl groups such as a 3,3,3-trifluoro-n-propyl group, a 2,2,2,2',2',2'-hexafluoroisopropyl group and a heptafluoroisopropyl group; and halogenated aryl groups such as o-, m- and p-chlorophenyl groups.

[0057] Group R 1 A monovalent hydrocarbon group may be included, which is preferably an alkyl group optionally substituted by a halogen atom and having 1 to 6 carbon atoms, more preferably having 1 or 2 carbon atoms, and more particularly a methyl group.

[0058] Group R 2 Examples include for the group R 1 Those specified.

[0059] Group R 2 Preferred is a hydrogen atom or an alkyl group optionally substituted by a halogen atom and having 1 to 10 carbon atoms, more preferably an alkyl group having 1 to 4 carbon atoms, and more particularly a methyl group or an ethyl group.

[0060] The polymer group Y includes polyoxyalkylenes as polymer chains, such as polyoxyethylene, polyoxypropylene, polyoxybutylene, polyoxytetramethylene, polyoxyethylene-polyoxypropylene copolymers and polyoxypropylene-polyoxybutylene copolymers; hydrocarbon polymers, such as polyisobutylene, polyethylene and copolymers of isoprene with polypropylene or polyisobutylene; polyurethanes; polyamides; polyacrylates; polymethacrylates; and polycarbonates. The polymer group Y is preferably bonded to the -[CH2-SiR2] group via -OC(=O)-NH- or -NH-C(=O)O-, -NH-C(=O)-NH-, -NR'-C(=O)-NH-, NH-C(=O)-NR'-, -NHC(=O)-, -C(=O)-NH-, -C(=O)-O-, -OC(=O)-, -OC(=O)-O-, -SC(=O)-NH-, -NH-C(=O)-S-, -C(=O)-S-, -SC(=O)-, -SC(=O)-S-, -C(=O)-, -S-, -O-, or -NR'-. 1 a (OR 2 ) 3-a ] one or more groups.

[0061] Herein, R' may be the same as or different from each other, and may be an alkyl group such as methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, n-pentyl, isopentyl, neopentyl, and tert-pentyl, a hexyl group such as n-hexyl, a heptyl group such as n-heptyl, an octyl group such as n-octyl, isooctyl, and 2,2,4-trimethylpentyl, a nonyl group such as n-nonyl, a decyl group such as n-decyl, a dodecyl group such as n-dodecyl, and an octadecyl group such as n-octadecyl; a cycloalkyl group such as a cyclopentyl group, a cyclohexyl group, a cycloheptyl group, and a methylcyclohexyl group; an alkenyl group such as a vinyl group, a 1-propenyl group, and a 2-propenyl group; an aryl group such as a phenyl group, a naphthyl group, an anthracenyl group, and a phenanthrenyl group; an alkylaryl group such as o-tolyl, m-tolyl, and p-tolyl, a xylyl group, and an ethylphenyl group; and an aralkyl group such as a benzyl group, an α- and β-phenylethyl group.

[0062] Examples of the substituent R' include halogenated alkyl groups such as a 3,3,3-trifluoro-n-propyl group, a 2,2,2,2',2',2'-hexafluoroisopropyl group, and a heptafluoroisopropyl group; and halogenated aryl groups such as o-, m-, and p-chlorophenyl groups.

[0063] The group R' may comprise a monovalent hydrocarbon group, preferably optionally substituted by halogen atoms and having 1 to 6 carbon atoms, more preferably an alkyl group having 1 or 2 carbon atoms, and more particularly a methyl group.

[0064] The group R' may be -CH(COOR")-CH2-COOR", wherein R" may be identical to or different from one another and have the meaning given for R'.

[0065] The group R" is preferably an alkyl group having 1 to 10 carbon atoms, more preferably a methyl group, an ethyl group or a propyl group.

[0066] More preferably, the group Y in formula (1) comprises a polyoxypropylene-containing urethane group or a polyoxypropylene group.

[0067] The silane-modified polymer (A) may have -[(CH 2 )-SiR 1 a (OR 2 ) 3-a ], for example, in the chain and / or at the terminal, preferably in the chain and at the terminal, and more preferably at the terminal.

[0068] -[(CH2)-SiR 1 a (OR 2 ) 3-aThe number of )] groups is not particularly limited and may be 1.5 or more and 2.2 or less, and more preferably 1.7 or more and 2.1 or less.

[0069] Component (A) may be a molecular chain having -[(CH2)-SiR 1 a (OR 2 ) 3-a ] groups.

[0070] In a particularly preferred embodiment of the present invention, the silane-modified polymer (A) comprises a silane-terminated polyether, more particularly a silane-terminated polypropylene glycol, having dimethoxymethylsilyl terminal groups bonded via groups of -OC(=O)-NH-(CH2) or -NH-C(=O)-NR'-(CH2) (the same definition specified above also applies to R').

[0071] The number average molecular weight Mn of the silane-modified polymer (A) may preferably be 400 or more and 30,000 or less, and preferably 1,000 or more and 30,000 or less, more preferably 10,000 or more and 30,000 or less, and still more preferably 10,000 or more and 19,000 or less.

[0072] The viscosity of the silane-modified polymer (A) measured at 20° C. in any case is preferably at least 0.2 Pa·s, more preferably at least 1 Pa·s, and most preferably at least 5 Pa·s, and is preferably 1,000 Pa·s or less, more preferably 700 Pa·s or less.

[0073] If the viscosity is 5 Pa·s or more and 100 Pa·s or less, it is even more preferred. The silane-modified polymer (A) having a lower viscosity has a relatively shorter polymer chain length and a higher content of -[(CH2)-SiR 1 a (OR 2 ) 3-a ] groups, which facilitate crosslinking. Therefore, the use of a silane-modified polymer (A) having a lower viscosity can provide a cured product having a higher crosslinking density and better tensile strength and elongation.

[0074] In a first particularly preferred embodiment of the present invention, the silane-modified polymer (A) comprises as polymer group Y a linear or branched polyoxyalkylene group, more preferably the chain ends of which are bonded to -[(CH2)-SiR 1 a (OR 2 ) 3-aIn this context, preferably at least 85%, more preferably at least 90%, and more particularly at least 95% of the entire chain ends are bonded to -[(CH2)-SiR 1 a (OR 2 ) 3-a ] group.

[0075] The number average molecular weight Mn of the polyoxyalkylene group Y is 200-30,000, preferably 10,000-19,000. Suitable methods for preparing such silane-modified polymers (A) and examples of silane-modified polymers (A) are already known and described in publications, including EP1535940B1 and EP1896523B1, which are incorporated herein by reference in their entirety. Corresponding silane-terminated polymers are also commercially available, for example commercially available from Wacker Chemie AG under the product name GENIOSIL (registered trademark) STP-E.

[0076] When the silane-modified polymer (A) is chemically synthesized, it can be synthesized by various known production methods using, for example, an addition reaction such as hydrosilylation, Michael addition reaction, or Diels-Alder addition reaction, or a reaction between an isocyanate-crosslinkable compound and a compound containing an isocyanate-reactive group.

[0077] The content of the silane-modified polymer (A) relative to the whole composition is not particularly limited, and for example, preferably in the range of 5 parts by mass or more and 90 parts by mass or less, more preferably in the range of 5 parts by mass or more and 80 parts by mass or less, and even more preferably in the range of 10 parts by mass or more and 70 parts by mass or less. This is because if its content is 5 parts by mass or more, the following effects can be obtained: in addition to the components forming the polymer matrix, no component remains in the composition in large quantities; fully exhibit the desired characteristics as a composition; the amount of the polymer matrix to be formed is sufficient so that the desired mechanical properties, such as tensile strength, elongation and tear strength become sufficient; defects in the cured product (such as adhesion failure, film cracking, etc.) are unlikely to occur; and the possibility of adverse effects caused by unexpected components is reduced. More preferably, its content is in the range of 10 parts by mass or more and 60 parts by mass or less. When the moisture curable composition of the present invention is used as an adhesive or a sealing material, it is preferred to add hydrophobized inorganic particles to the composition, which will be described later, to impart appropriate thixotropy. In order to mix a sufficient amount of the filler with the composition, the amount of component (A) to be added preferably falls within the above range.

[0078] Component (B):

[0079] The polymer (B) in the present invention is a (meth)acrylate polymer (i.e., a polymer of (meth)acrylic acid ester) containing a crosslinkable silyl group in the molecule. The crosslinkable silyl group may be introduced at the end of the main chain of the (meth)acrylate polymer or introduced into the side chain thereof, or may be introduced at the end of the main chain and introduced into the side chain.

[0080] The crosslinkable silyl group contained in component (B) has a structure represented by the following formula (2):

[0081] -SiR 1 a X 3-a (2)

[0082] Where a is 0, 1 or 2; R 1 The same as those defined in the above formula (1), and preferably methyl, ethyl or propyl, particularly preferably methyl. X each independently represents a hydroxyl group or a hydrolyzable group. The number of a can be appropriately determined according to the reactivity of component (B), etc. For example, in applications requiring a certain strength, a is preferably designed to be zero (0) because the crosslinking point can be increased. In applications where its reactivity is suppressed or the elongation of its cured product is required, a is preferably designed to be 1 or 2.

[0083] Specific examples of X include hydroxyl, hydrogen atom, halogen atom, alkoxyl, acyloxy, ketoxime ester (ketoxymate) group, amino, amide, acid amide, aminooxy, sulfhydryl and alkenyloxy. Among them, alkoxy such as methoxy or ethoxy is more preferred, and methoxy or ethoxy is particularly preferred because hydrolyzability is moderate and makes the handling of the compound easy.

[0084] Crosslinkable silyl groups (SiR 1 a X 3-a) include, but are not limited to, trimethoxysilyl, triethoxysilyl, tri(2-propenyloxy)silyl, triacetoxysilyl, dimethoxymethylsilyl, diethoxymethylsilyl, dimethoxyethylsilyl, (chloromethyl)dimethoxysilyl, (chloromethyl)diethoxysilyl, (methoxymethyl)dimethoxysilyl, (methoxymethyl)diethoxysilyl, (N,N-diethylaminomethyl)dimethoxysilyl, and (N,N-diethylaminomethyl)diethoxysilyl. Among them, methyldimethoxysilyl, trimethoxysilyl, triethoxysilyl, (chloromethyl) dimethoxysilyl, (methoxymethyl) dimethoxysilyl, (methoxymethyl) diethoxysilyl and (N, N-diethylaminomethyl) dimethoxysilyl are preferred because they show high activity, and a cured product with good mechanical properties can be obtained from a composition comprising component (B) having such a group. From the viewpoint of activity, trimethoxysilyl, (chloromethyl) dimethoxysilyl and (methoxymethyl) dimethoxysilyl are particularly preferred. From the viewpoint of stability, methyldimethoxysilyl, methyldiethoxysilyl and triethoxysilyl are particularly preferred. From the viewpoint of safety, methyldiethoxysilyl and triethoxysilyl are particularly preferred. Due to ease of production, trimethoxysilyl, triethoxysilyl and dimethoxymethylsilyl are more preferred.

[0085] From the viewpoint of strength after curing, the average number of crosslinkable silyl groups per molecule in component (B) is preferably 0.2 or more, more preferably 0.4 or more, and still more preferably 0.7 or more. Since the elongation of the cured product tends to be better, the average number of crosslinkable silyl groups is preferably 4.0 or less, more preferably 3.0 or less. The average number of crosslinkable silyl groups per molecule of component (B) may be 0.2 or more and 4.0 or less, and more preferably 0.7 or more and 3.0 or less.

[0086] The (meth)acrylate polymer (B) may include a (meth)acrylate monomer as a monomer unit constituting the main chain, and the (meth)acrylate monomer may be a monomer having an alkyl group having 1 to 5 carbon atoms bonded to the (meth)acrylate. The (meth)acrylate monomer constituting the main chain is not limited to a specific monomer, and one type thereof may be used alone, or two or more types thereof may be used in combination. When component (B) is a copolymer chain formed by polymerization of two or more types of (meth)acrylate monomers, the (meth)acrylate monomer may form a block polymer or a random polymer by polymerization.

[0087] Examples of (meth)acrylate monomers include methyl (meth)acrylate, ethyl (meth)acrylate, propyl (meth)acrylate, butyl (meth)acrylate, isobutyl (meth)acrylate, tert-butyl (meth)acrylate, hexyl (meth)acrylate, octyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, propyl (meth)acrylate, octyl (meth)acrylate, and isodecyl (meth)acrylate. Among these, methyl (meth)acrylate, ethyl (meth)acrylate, and butyl (meth)acrylate are preferred, and methyl (meth)acrylate is more preferred because water-resistant adhesion tends to be favorable.

[0088] In the (meth)acrylate monomer, the alkyl group bonded to the (meth)acrylate preferably has 1 to 5 carbon atoms, more preferably 1 to 3 carbon atoms, particularly preferably 1 carbon atom. When the number of carbon atoms falls within the above range, the adhesion properties before and after water immersion after curing of the moisture curable composition become better.

[0089] It is particularly preferred to use a compound as component (B) which is a polymer containing a methyl (meth)acrylate monomer as a monomer unit and having a trimethoxysilyl group. In this case, both the normal tensile adhesive strength and the water-resistant tensile adhesive strength (which will be described later) can be set to 1.0 N / mm 2 or higher, and can express a property in which the water-resistant tensile adhesive strength becomes greater than the normal tensile adhesive strength.

[0090] Component (B) can be synthesized by a known method, or commercially available polymers can be used as component (B). Examples of commercially available products that can be used as component (B) include XMAP series (product name of Kaneka), ARUFON US-6000 series (product name of Toagosei, including US-6110, US-6120, etc.) and ACTFLOW NE series (product name of Soken Chemical & Engineering Co., Ltd., including NE-1000, NE-3000, etc.).

[0091] The molecular weight of component (B) is not limited to a specific value, and may be, for example, 1,000 or more and 100,000 or less, more preferably 1,000 or more and 50,000 or less, and still more preferably 1,000 or more and 10,000 or less. When the molecular weight of component (B) falls within the above range, the viscosity of the moisture curable composition tends to be sufficiently low, and its workability tends to be excellent.

[0092] The content of component (B) relative to the entire composition is not particularly limited, and, for example, is preferably in the range of 5 parts by mass or more and 90 parts by mass or less, more preferably in the range of 5 parts by mass or more and 80 parts by mass or less, and even more preferably in the range of 10 parts by mass or more and 70 parts by mass or less. This is because if its content is 5 parts by mass or more, the following effects can be obtained: no component other than the component forming the polymer matrix remains in the composition in a large amount; the desired characteristics as a composition are fully exhibited; the amount of the polymer matrix to be formed is sufficient so that the desired mechanical properties, such as tensile strength, elongation and tear strength become sufficient; defects in the cured product (such as adhesion failure, film cracking, etc.) are less likely to occur; and the possibility of adverse effects due to unexpected components is reduced. More preferably, its content is in the range of 10 parts by mass or more and 60 parts by mass or less.

[0093] When the moisture curable composition of the present invention is used as an adhesive or a sealing material, it is preferred to add hydrophobized inorganic particles to the composition, which will be described later, to impart appropriate thixotropy. In order to mix a sufficient amount of filler with the composition, the amount of component (B) to be added preferably falls within the above range.

[0094] Component (C):

[0095] The amine-based catalyst (C) in the present invention is a curing catalyst having at least one alkoxy group, and also functions as an adhesion promoter.

[0096] In the moisture-curable composition of the present invention, a catalyst other than component (C) may be used in combination, but it is desirable not to use a catalyst containing a metal from the viewpoint of environment and safety.

[0097] Component (C) may be, for example, an alkoxyamine, an aralkyloxyamine or an aminosilane having an alkoxy group. Among them, an aminosilane having an alkoxy group is particularly preferred.

[0098] Examples of the alkoxyamines include 2-(2-aminoethoxy)ethanol, ethanolamine, trishydroxymethylaminomethane, methoxyamine, and ethoxyamine.

[0099] Examples of aminosilanes include aminopropyltrimethoxysilane, aminopropyltriethoxysilane, aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, N-(2-aminoethyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)aminopropyltriethoxysilane, N-(2-aminoethyl)aminopropylmethyldimethoxysilane, N-(2-aminoethyl)aminopropylmethyldiethoxysilane, N-cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminomethylmethyldiethoxysilane, N-cyclohexylaminomethyltrimethoxysilane, and N-cyclohexylaminomethylmethyldimethoxysilane. When any of these aminosilanes is used, a moisture-curable composition with a suitable curing rate can be obtained.

[0100] The number of amino groups in component (C) is not particularly limited as long as it is one or more. When two or more amino groups are contained, the adhesive strength tends to be further improved.

[0101] When suitable adhesive properties are required in a composition comprising the above components (A) and (B), component (C) preferably has a plurality of amino groups. Examples of component (C) include N-(2-aminoethyl)aminopropyltrimethoxysilane, N-(2-aminoethyl)aminopropyltriethoxysilane, N-(2-aminoethyl)aminopropylmethyldimethoxysilane, and N-(2-aminoethyl)aminopropylmethyldiethoxysilane.

[0102] When discoloration (e.g., yellowing) of a cured product obtained using a composition comprising the above-mentioned components (A) and (B) is suppressed as much as possible, component (C) preferably has one amino group. Examples of component (C) include 2-(2-aminoethoxy)ethanol, ethanolamine, trimethylolaminomethane, methoxyamine, ethoxyamine, aminopropyltrimethoxysilane, aminopropyltriethoxysilane, aminopropylmethyldimethoxysilane, aminopropylmethyldiethoxysilane, N-cyclohexylaminomethyltriethoxysilane, N-cyclohexylaminomethylmethyldiethoxysilane, N-cyclohexylaminomethyltrimethoxysilane, and N-cyclohexylaminomethylmethyldimethoxysilane.

[0103] The amine-based catalyst (C) in the present invention is not limited to the above-mentioned alkoxyamines, aralkyloxyamines and aminosilanes having an alkoxy group, and may be any amine-based catalyst capable of curing the composition to exhibit adhesive properties by the same mechanism.

[0104] The amine-based catalyst (C) in the present invention may be used as a curable catalyst and / or an adhesion enhancer in the moisture curable composition according to the present invention.

[0105] The amine-based catalyst (C) used according to the present invention is a commercially available product and can be produced by a generally used chemical process.

[0106] Component (C) is not particularly limited relative to the content of the whole moisture curable composition, and preferably, for example, in the range of 0.1 mass parts or more to 10 mass parts or less. When its content is 0.1 mass parts or more, the hydrolysis and condensation reaction of the silane-modified polymer can be accelerated. On the other hand, if this content is less than 0.1 mass parts, the effect of catalytic hydrolysis and condensation reaction is reduced, and at the same time, the adhesive properties shown are reduced. If the content exceeds 10 mass parts, hydrolysis and condensation reaction may be carried out during the storage of the moisture curable composition, and storage stability may deteriorate, resulting in gelling, curing, etc. during storage. More preferably, its content is in the range of 0.5 mass parts or more and 5 mass parts or less.

[0107] Other ingredients in the moisture curable composition:

[0108] The form and composition content of the moisture-curable composition used as an adhesive or sealing material for various substrates for various applications are not limited.

[0109] As an adhesive composition suitable for substrates in typical applications such as building materials and industrial constructions, the following compositions are preferred.

[0110] (A): 5 parts by mass or more and 90 parts by mass or less,

[0111] (B): 5 parts by mass or more and 90 parts by mass or less,

[0112] (C): 0.01 parts by mass or more and 10 parts by mass or less,

[0113] (D): Plasticizer: 0 parts by mass or more and 50 parts by mass or less

[0114] (E): Dehydrating agent: 0 parts by mass or more and 10 parts by mass or less,

[0115] (F): Adhesion promoter: 0 parts by mass or more and 5 parts by mass or less,

[0116] (G): Hydrophobized inorganic particles: 0.1 parts by mass or more and 20 parts by mass or less,

[0117] (H): Filler: 0 parts by mass or more and 80 parts by mass or less, and

[0118] (I): Stabilizer: 0.01 parts by mass or more and 5 parts by mass or less.

[0119] The amount of each component in parts by mass represents a value relative to 100 parts by mass of the entire moisture-curable composition.

[0120] Component (D):

[0121] Plasticizer (D) is a component having the function of regulating the viscosity and viscous properties of the moisture curable composition of the present invention, and can also be used as a reagent for regulating physical properties such as tensile strength and elongation, or as an additive for improving the flexibility and weather resistance of the cured product. If the above-mentioned function or effect is not required, the component is not an essential component of the moisture curable composition of the present invention. Plasticizer (D) can be purchased as a commercial product, and can also be prepared by conventional chemical methods.

[0122] Examples of the plasticizer (D) include phthalates such as dioctyl phthalate, diisooctyl phthalate and didecyl phthalate; perhydrophthalates such as diisononyl 1,2-cyclohexanedicarboxylate and dioctyl 1,2-cyclohexanedicarboxylate; adipates such as dioctyl adipate; benzoates; glycol esters; esters of saturated alkanediols such as 2,2,4-trimethyl-1,3-pentanediol monoisobutyrate and 2,2,4-trimethyl-1,3-pentanediol diisobutyrate; phosphates; sulfates; polyesters; polyethers such as polyethylene glycol and polypropylene glycol, preferably having a molecular weight of 100 to 10,000 g / mol; polystyrene; polybutadiene; polyisobutylene; paraffin hydrocarbons; and branched macromolecular hydrocarbons.

[0123] The content of the plasticizer (D) relative to the entire composition may be zero (not included), but is preferably in the range of 0 to 50 parts by mass. This is because if the content exceeds 50 parts by mass, there is a possibility of causing adverse effects such as deterioration of the physical properties of the cured product, and the possibility of causing curing failure and an uncured state after application. More preferably, the content of the plasticizer (D) is in the range of 0 to 30 parts by mass.

[0124] Component (E):

[0125] The dehydrating agent (E) is a component that can cause dehydration by capturing water in the moisture curable composition of the present invention.

[0126] The dehydrating agent (E) can be purchased as a commercial product, and can also be prepared by a common chemical method.

[0127] The dehydrating agent (E) may be used alone, or a mixture of two or more types thereof may be used in combination.

[0128] Examples of component (E) include silanes such as vinyltrimethoxysilane, vinyltriethoxysilane, vinylmethyldimethoxysilane, O-methylcarbamate-methyldimethoxysilane, O-methylcarbamate-trimethoxysilane, O-ethylcarbamate-methyldiethoxysilane and O-ethylcarbamate-triethoxysilane, and / or partial condensates thereof, and orthoesters such as 1,1,1-trimethoxyethane, 1,1,1-triethoxyethane, trimethoxymethane and triethoxymethane.

[0129] The content of the dehydrating agent (E) relative to the entire composition may be zero (not included), but is preferably in the range of 0.01 to 10 parts by mass. This is because if its content is less than 0.01 parts by mass, the dehydrating effect is insufficient, and there is a possibility that defects such as thickening, gelation, and curing occur during production and storage, and if its content exceeds 10 parts by mass, there is a possibility that adverse effects such as deterioration of the physical properties of the cured product may occur, and there is also a possibility that curing failure and an uncured state after application may occur. More preferably, the content of the dehydrating agent (E) is in the range of 0.5 to 3.0 parts by mass.

[0130] Component (F):

[0131] Adhesion promoter (F) is a component having a function as a curing co-catalyst and can also serve as an adhesion enhancer for moisture curable compositions of the present invention. Adhesion promoter (F) is not particularly limited in its structure and molecular weight, and can be purchased as a commercial product, and can also be prepared by commonly used chemical methods. Adhesion promoter (F) can be used alone, or a mixture of two or more types thereof can be used in combination.

[0132] Examples of adhesion promoters (F) may include organic silicon compounds such as epoxy silanes and isocyanurate silanes. Representative examples include 3-glycidyloxypropyltrimethoxysilane, 3-glycidyloxypropyltriethoxysilane, tris(3-trimethoxysilylpropyl)isocyanurate, and triglycidyl isocyanurate.

[0133] The content of the adhesion promoter (F) relative to the entire composition may be zero (not included), but is preferably in the range of 0.01 to 5 parts by mass. This is because if the content exceeds 5 parts by mass, there is a possibility of causing adverse effects such as deterioration of the physical properties of the coating film, and a possibility of causing curing failure and an uncured state after application.

[0134] Component (G):

[0135] The optionally mixed hydrophobized inorganic particles (G) form a network in the system by van der Waals force to thicken the entire system, thereby imparting a certain degree of thixotropic properties to the moisture-curable composition of the present invention.

[0136] Examples of inorganic particles used as a raw material for the hydrophobized inorganic particles (G) include inorganic particles such as silicon dioxide, titanium dioxide, bentonite, zinc oxide, talc, kaolin, mica, vermiculite, magnesium carbonate, calcium carbonate, aluminum silicate, barium silicate, calcium silicate, magnesium silicate, strontium silicate, tungstate metal salts, magnesium, zeolite, barium sulfate, calcined calcium sulfate, calcium phosphate, fluoroapatite, hydroxyapatite, and metal soaps.

[0137] Furthermore, composite particles obtained by coating particles with a metal oxide or the like, or modified particles whose surfaces are treated with a compound or the like may be used.

[0138] Generally, on the surfaces of these particles, there are portions covered with hydrophilic groups such as silanol groups, carbinol groups or other hydroxyl groups, and portions covered with groups obtained by hydrophobizing the above groups with an alkyl group or the like or with other hydrophobic groups.

[0139] By adjusting the ratio of hydrophilic groups to hydrophobic groups, the cohesion and solubility of inorganic particles in the system can be controlled.

[0140] In inorganic particles, silicon dioxide is preferably used. Exemplary types of silicon dioxide include fumed silica, wet silica and colloidal silica. On the surface of the particles of any type of silicon dioxide, there is hydrophilic silanol, and its silanol group can be hydrophobically treated with an alkyl group etc. in an optional ratio. Therefore, it is easy to set the mol ratio of the hydrophilic group and the hydrophobic group on the surface. From the viewpoint of using aggregated structure, high affinity with various types of oil, availability and cost efficiency, silicon dioxide is preferred. This is because it makes it possible to be widely used.

[0141] In the present invention, the silica most preferably used is fumed silica.

[0142] Fumed silica particles have a multi-dimensional aggregate structure. Therefore, the balance between hydrophilic and hydrophobic groups on the surface can be controlled according to their aggregation level, and the aggregated units can be recombined.

[0143] Since the fumed silica particles have a porous structure, the surface area is large, and the functions of association and adsorption are enhanced. Therefore, the system using the fumed silica particles can be produced more stably and uniformly.

[0144] In the fumed silica particles, a primary particle as the smallest unit generally has a size of about 5 to 30 nm. The primary particles aggregate to form primary aggregates, that is, secondary particles.

[0145] The size of the primary aggregate is generally about 100-400 nm. Since the primary particles are fused by chemical bonds, it is generally difficult to separate the primary aggregates from each other. Aggregated structures are formed from the primary aggregates, which are referred to as secondary aggregates, i.e., tertiary particles. The size of the secondary aggregates is generally about 10 μm. The aggregation form between the primary aggregates in the secondary aggregates is generally not derived by chemical bonds but by hydrogen bonds and van der Waals forces.

[0146] When the fumed silica particles are in powder form, secondary aggregates are usually in the largest aggregate state. However, secondary aggregates can be further aggregated in moisture curable compositions. That is, in one example of the present invention, hydrophobized silica effectively forms a network of hydrophobic parts about silane-terminated modified polymers and reactive materials (reactive diluents) by van der Waals forces. The force used to separate this aggregate is less than the force of separating secondary aggregates. That is, in one example of the present invention, when applying moisture curable compositions with a combing trowel, aggregates are separated to reduce viscosity during application.

[0147] Preferably, the fumed silica particles are hydrophobic or hydrophobized. The A component used in the hydrophobization is not particularly limited. For example, the component used in the hydrophobization can be made hydrophobic by known methods such as treating with halogenated organosilicon (e.g., methyltrichloromethane), alkoxysilane (e.g., dimethyldialkoxysilane), silazane or low molecular weight methylpolysiloxane.

[0148] The content of the hydrophobized inorganic particles (G) may be zero (not included) relative to the entire composition, but is desirably 0.1 to 20 parts by mass. This is because if its content exceeds 20 parts by mass, the viscosity of the entire system increases, and there is a possibility that the system becomes uneven due to insufficient stirring during the production process of the moisture curable composition, and the workability during the application process may be significantly reduced. Its content is more preferably in the range of 1 to 10 parts by mass, and further preferably in the range of 2 to 5 parts by mass.

[0149] Component (H):

[0150] The filler (H) optionally added has the function of an extender, regulating viscosity or viscosity and regulating the physical properties of the moisture curable composition of the present invention such as tensile strength and elongation, and can serve as a curing accelerator for coating materials through the moisture contained. Filler (H) is a component different from component (G). When the above-mentioned function and effect are unnecessary, when the moisture curable composition of the present invention is used as a coating composition, the component is not an essential component.

[0151] The filler (H) can be purchased as a commercial product, and can also be prepared by a common chemical method.

[0152] The filler (H) may be used alone, or a mixture of two or more types thereof may be used in combination.

[0153] The filler (H) is not limited as long as it exhibits the aforementioned functions and effects. Examples of the filler (H) include non-reinforcing fillers, preferably having a BET surface area of ​​at most 50 m 2 / g fillers, such as quartz, silica sand, diatomaceous earth, calcium silicate, zirconium silicate, talc, kaolin and zeolite; metal oxide powders, including aluminum oxide, titanium oxide, iron oxide or zinc oxide, and / or mixed oxides thereof; barium sulfate, calcium carbonate, gypsum, silicon nitride, silicon carbide, boron nitride; glass powder; and polymer powders, such as polyacrylonitrile powder; reinforcing fillers, and BET surface areas exceeding 50m 2 / g fillers, for example silica prepared by pyrogenic treatment, precipitated silica, precipitated calcium carbonate, ground calcium carbonate, carbon black (e.g. furnace black and acetylene black), and mixed silicon / aluminum oxides with a high BET surface area; fillers in the form of hollow beads of aluminum trihydroxide, for example magnetic microbeads, exemplified by the products available under the trade name Zeeospheres (registered trademark) from 3M Deutschland GmbH, Neuss, Germany, elastic polymer beads of this type, available under the trade name EXPANCEL (registered trademark) from AKZONOBEL, Expancel, Sundsvall, Sweden, or glass beads; and fillers in the form of fibers, for example asbestos and / or polymer fillers.

[0154] For example, the above fillers can be hydrophobized by treatment with organosilanes and / or organosiloxanes or with stearic acid or by etherification of hydroxyl groups into alkoxy groups.

[0155] The filler (H) is preferably calcium carbonate, talc, aluminum hydroxide or silicon dioxide, particularly preferably calcium carbonate. Preferred grades of calcium carbonate are ground or precipitated calcium carbonate and are optionally surface treated with a fatty acid such as stearic acid or its salts. Preferred silicon dioxide is pyrogenic (fumed) silicon dioxide.

[0156] The filler (H) preferably has a water content of less than 1 part by mass, more preferably less than 0.5 part by mass.

[0157] The content of filler (H) relative to the entire composition is preferably in the range of 0 to 80 parts by mass, and more preferably in the range of 0 to 60 parts by mass. When its content falls within the above range, defects of the coating material such as poor adhesion and film rupture are hardly caused, and the viscosity during production is appropriate. Therefore, uniform stirring can be achieved.

[0158] Component (I):

[0159] The stabilizer (I) is a component having the function of an ultraviolet absorber, an antioxidant, a heat stabilizer, or a light stabilizer for use in the moisture-curable composition of the present invention, and can also function as a stabilizer for preventing polymer degradation.

[0160] The stabilizer (I) can be purchased as a commercial product, and can also be prepared by a common chemical method.

[0161] The stabilizer (I) may be used alone, or a mixture of two or more types thereof may be used in combination.

[0162] The stabilizer (I) is not limited as long as it exhibits the above-mentioned functions and effects, and is preferably an antioxidant, a UV stabilizer or a HALS.

[0163] The content of the stabilizer (I) relative to the entire composition is preferably in the range of 0.01 to 5 parts by mass. This is because if its content is less than 0.01 parts by mass, the coating film may deteriorate due to ultraviolet light, heat, oxidation, etc., and if its content exceeds 5 parts by mass, it may cause unexpected problems such as color change in transparent products. Its content is more preferably 0.5 to 2.0 parts by mass.

[0164] The moisture-curable composition of the present invention may include one or two or more selected from the group consisting of octamethylcyclotetrasiloxane (D4), decamethylcyclopentasiloxane (D5), dodecamethylcyclohexasiloxane (D6), tetradecamethylcycloheptasiloxane (D7) and hexadecamethylcyclooctasiloxane (D8).

[0165] The sum of the respective contents of (D4), (D5), (D6), (D7) and (D8) may be less than 0.1 parts by mass (ie, less than 1,000 ppm) relative to 100 parts by mass of the entire moisture curable composition.

[0166] When the sum of the contents of (D4) to (D8) in the moisture curable composition falls within the above range, the flash point of the composition as a whole becomes high, and safety during storage can be improved.

[0167] When the sum of the contents of (D4) to (D8) is designed to be less than 0.1 parts by mass relative to 100 parts by mass of the entire moisture-curable composition, the moisture-curable composition can be prepared by using components serving as components (A), (B) and (C) and containing (D4) to (D8) in a total content of less than 0.1% by mass.

[0168] The contents of (D4) to (D8) are determined by gas chromatography. The measurement conditions of the gas chromatography can be appropriately selected according to a conventionally known method.

[0169] Methods for reducing the content of (D4)-(D8) in components (A)-(C) include methods of heating under reduced pressure, which are well known. For example, when preparing raw materials for components (A) to (C), it is desirable to perform heat treatment under reduced pressure at 180°C and 20 mmHg for about 8 hours.

[0170] The moisture curable composition of the present invention may contain optional components in addition to the above components, as long as the purpose of the present invention is achieved. For example, the moisture curable composition of the present invention may contain a deformation agent, a curing rate regulator, an additive for this type of composition, and any other suitable material.

[0171] The present invention also provides a method for improving water-resistant adhesion by bonding a substrate and a cured product obtained by curing a moisture curable composition, the moisture curable composition comprising:

[0172] Component (A) which is a silane-modified polymer represented by the general formula (1):

[0173] Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0174] (wherein Y is an x-valent polymer group bonded via nitrogen, oxygen or sulfur,

[0175] R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups,

[0176] R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group,

[0177] x is an integer from 1 to 10, and;

[0178] a is 0, 1, or 2);

[0179] Component (B) which is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule; and

[0180] Component (C) which is an amine-based catalyst having at least one alkoxy group.

[0181] The method comprises: using a moisture-curable composition comprising component (B), wherein component (B) is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule, so that after completing a water immersion test, the tensile bonding strength between the substrate and the cured product reaches 1.0 times or more of that before the water immersion test, in which the substrate and the cured product are immersed in water at 23° C. for 168 hours.

[0182] Water-resistant adhesion can be evaluated as follows. The tensile adhesion strength of the sample after curing at 23°C for 168 hours is measured. The sample after curing at 23°C for 168 hours is immersed in distilled water at 23°C for 168 hours, taken out of the distilled water, and aged at 23°C for 168 hours, and the tensile adhesion strength of the sample is measured.

[0183] By curing, the moisture curable composition can be used as an adhesive or a sealing material for bonding substrates.

[0184] The present invention also relates to a laminate including a substrate and a cured product obtained by applying a moisture curable composition to the substrate and curing the moisture curable composition.

[0185] The substrate to which the moisture curable composition of the present invention is applied for bonding is not particularly limited. The substrate may be concrete, mortar, gypsum board, cork board, wood cement board, calcium silicate board or tile. The substrate may be pre-treated with a primer.

[0186] The present invention is a method for producing a laminate including a first substrate, a second substrate, and a cured product of bonding the first substrate to the second substrate, the method comprising:

[0187] applying the moisture curable composition described above onto a surface of a first substrate; and

[0188] The second substrate is contacted with the moisture curable composition, and the moisture curable composition is then cured to form a cured product.

[0189] Example

[0190] The present invention will be specifically described with reference to Examples and Comparative Examples based on the results shown in Tables 1 and 2. However, the present invention is not limited to the following Examples.

[0191] Method for preparing samples for evaluating stretch bond performance:

[0192] The method for preparing the samples was in accordance with JIS A 5536.

[0193] The adhesive tape defined by JISZ 1525 is connected to the four sides of substrate A so that the width of the adhesive tape covering substrate A is 7mm, and the smooth surface of substrate A faces upward. An appropriate amount of moisture curable composition is placed on substrate A, and the SS330 combing trowel defined by JIS G 3101 is erected obliquely, and then pulled toward the user with the user's hand to evenly apply the moisture curable composition to substrate A. After applying the moisture curable composition, the adhesive tape is immediately separated and removed. After applying the moisture curable composition, substrate B is placed so that the moisture curable composition is placed between substrates A and B, and a weight of about 1kg is placed on substrate B so that the film of the moisture curable composition is compressed to a thickness of about 1mm. Therefore, the moisture curable composition is in close contact with substrates A and B. The moisture curable composition is then aged under the following aging conditions A or B.

[0194] One day before the tensile bond strength measurement test, an appropriate amount of epoxy resin (water-immersed epoxy resin, purchased from CEMEDINE CO., LTD.) was applied to the substrate B of the sample (on the side where the moisture curable composition was not applied), and a stainless steel fixture for tensile testing (SS400, 10 mm × 40 mm × 40 mm, M10 nut welding) was fixed in place.

[0195] Substrate A: ISO mortar (70mm×70mm×20mm)

[0196] Substrate B: Aluminum (A5052, 25mm×60mm×2mm) cleaned with ethanol

[0197] Aging condition A: Normal adhesion

[0198] The sample in which the substrates A and B were bonded by the moisture curable composition was aged for 168 hours under the conditions of a temperature of 23° C. and a relative humidity of 50%. Immediately thereafter, a tensile test was performed.

[0199] Aging Condition B: Water-Resistant Adhesion

[0200] The sample in which the substrates A and B were bonded by the moisture curable composition was aged for 168 hours under the conditions of a temperature of 23° C. and a relative humidity of 50%. The sample was then immersed in water. For the water immersion, the sample was immersed in distilled water so that the distance from the upper part of the sample to the water surface was about 3.5 cm, and then the sample was allowed to stand at 23° C. for 168 hours. After the immersion, the sample was aged at 23° C. and a relative humidity of 50% for 168 hours, and a tensile test was performed.

[0201] Method used to evaluate tensile bond strength:

[0202] The tensile adhesive strength of the sample prepared by the method of preparing a sample for evaluating tensile adhesive performance was measured and evaluated by the following apparatus under the following measuring conditions.

[0203] Evaluation device: Desktop precision universal testing machine (Autograph AGS-X series (manufactured by Shimadzu Corporation))

[0204] Stretching rate: 1mm / min

[0205] Unit of measurement: Tensile bond strength (N / mm) calculated from the maximum load before breaking (N) 2 )

[0206] After the sample was aged under aging condition A, the normal state adhesion was evaluated by the above method. 0.75 N / mm 2 The tensile bond strength of 100 N / mm2 or more is acceptable. The tensile bond strength measurement result obtained at this time is referred to as the "normal tensile bond strength (N / mm2)". 2 )”.

[0207] After aging the samples under aging condition B, the water-resistant adhesion was evaluated by the above method. 0.50 N / mm 2 The tensile bond strength of 100 N / mm2 or more is acceptable. The tensile bond strength measurement result obtained at this time is referred to as "water-resistant tensile bond strength (N / mm2)". 2 )”.

[0208] Method used to evaluate water-resistant adhesion:

[0209] Preferably, the normal tensile bond strength (N / mm 2 ) divided by the water-resistant tensile bond strength (N / mm 2 ) results in a value of 1.0 or greater.

[0210] Methods for evaluating rubber properties:

[0211] The tensile strength of the moisture curable composition was evaluated according to JIS K 6251. 1.5 N / mm 2 A tensile strength of 1000 Nm or greater is acceptable.

[0212] The elongation of the moisture curable composition was evaluated according to JIS K 6251. An elongation of 55 to 100% was determined to be acceptable.

[0213] Method for evaluating storage stability:

[0214] Immediately after the moisture curable composition was prepared, the moisture curable composition was stored at 50° C. for 28 days, and the appearance after storage was evaluated. When the appearance was determined to satisfy Category A, the storage stability was determined to be acceptable.

[0215] Category A: No aggregation or separation is observed in the moisture curable composition

[0216] Category B: Aggregation or separation observed in the moisture curable composition

[0217] Embodiment 1:

[0218] For the moisture curable composition, the following components were used.

[0219] 15.0 parts by mass of GENIOSIL (registered trademark) STP-E 30 (viscosity at 25° C.: 30,000 mPa·s) supplied by Wacker Chemie AG, wherein Y is a divalent organic polymer group bonded via a urethane group containing an oxyalkylene group, and R 1 and R 2 All of them are methyl, a is 1, and x is 2) as a silane-modified polymer (A), 10 parts by mass of a methyl (meth)acrylate polymer having three trimethoxysilyl groups in the side chain and at the terminal as a (meth)acrylate polymer (B), 2.5 parts by mass of GENIOSIL (registered trademark) GF96 supplied by Wacker Chemie AG as an amine-based catalyst (C), 21.0 parts by mass of polypropylene glycol (diol type, molecular weight: 400) purchased from FUJIFILM Wako Pure Chemical Corporation as a plasticizer (D), 2.0 parts by mass of GENIOSIL (registered trademark) XL 10 supplied by Wacker Chemie AG as a dehydrating agent (E), 2 parts by mass of GENIOSIL (registered trademark) GF 80 supplied by Wacker Chemie AG as an adhesion promoter (F), 2.5 parts by mass of Hydrophobic silica (HDK (registered trademark) H18) provided by AG as hydrophobized inorganic particles (G), 44.0 parts by mass of heavy calcium carbonate (SOFTON 2200) (provided by BIHOKU FUNKAKOGYO CO., LTD.) as filler (H), and 1.0 parts by mass of hindered amine Tinuvin B75 provided by BASF Japan Ltd. as stabilizer (I), and uniformly stirred to prepare moisture-curable composition 1.

[0220] GENIOSIL (registered trademark) GF 96 is 3-aminopropyltrimethoxysilane

[0221] GENIOSIL (registered trademark) XL 10 is vinyltrimethylpropane.

[0222] GENIOSIL (registered trademark) GF 80 is 3-glycidoxypropyltrimethoxysilane.

[0223] The normal state tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of the moisture curable composition 1 were within acceptable standards, and the moisture curable composition 1 was determined to be acceptable.

[0224] Embodiment 2:

[0225] The moisture-curable composition 2 was obtained using the same components, the same mass parts, and the same preparation method as in Example 1, except that 10 mass parts of an ethyl (meth)acrylate polymer containing three trimethoxysilyl groups in the side chain and at the terminal was used as the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0226] The normal tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of the moisture-curable composition 2 were within acceptable standards, and the moisture-curable composition 2 was determined to be acceptable. The water-resistant tensile adhesive strength and tensile strength of the moisture-curable composition 2 were lower than those in Example 1, but a high elongation was achieved.

[0227] Embodiment 3:

[0228] The moisture-curable composition 3 was obtained using the same components, the same mass parts and the same preparation method as in Example 1, except that 10 mass parts of a 2-ethylhexyl (meth)acrylate polymer containing three trimethoxysilyl groups in the side chain and the terminal was used as the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0229] The normal tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of the moisture-curable composition 3 were within the acceptable standards, and the moisture-curable composition 3 was determined to be acceptable. The water-resistant tensile adhesive strength and tensile strength of the moisture-curable composition 3 were lower than those in Examples 1 and 2, but a high elongation was achieved.

[0230] Embodiment 4:

[0231] The moisture-curable composition 4 was obtained using the same components, the same mass parts and the same preparation method as in Example 1, except that 10 mass parts of a stearyl (meth)acrylate polymer containing three trimethoxysilyl groups in the side chain and the terminal was used as the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0232] The normal tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of moisture-curable composition 4 were within acceptable standards, and moisture-curable composition 4 was determined to be acceptable. The water-resistant tensile adhesive strength and tensile strength of moisture-curable composition 4 were lower than those in Examples 1 and 2, but high elongation was achieved.

[0233] Embodiment 5:

[0234] Moisture-curable composition 5 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 2.5 parts by mass of GENIOSIL (registered trademark) GF 94 available from Wacker Chemie AG was used as an amine-based catalyst (C). The same evaluation as in Example 1 was performed.

[0235] GENIOSIL (registered trademark) GF 94 is 3-(2-aminomethylamino)propyltriethoxysilane.

[0236] The normal state tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of the moisture curable composition 5 were within acceptable standards, and the moisture curable composition 5 was determined to be acceptable.

[0237] Embodiment 6:

[0238] The moisture curable composition 6 was obtained by using the same components, the same mass parts and the same preparation method as in Example 1, except that 15.0 mass parts of GENIOSIL (registered trademark) STP-E 10 (viscosity at 25° C. was 10,000 mPa·s) provided by Wacker Chemie AG was used. In the above general formula (1), Y is a divalent organic polymer group bonded through a urethane group containing an oxyalkylene group, and R 1 and R 2 The same evaluation as in Example 1 was performed as the silane-modified polymer (A).

[0239] The normal state tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation, and storage stability of the moisture curable composition 6 were within acceptable standards, and the moisture curable composition 6 was determined to be acceptable.

[0240] When aminopropyltrimethoxysilane is used as component (C) as described above, the water-resistant tensile bond strength between the substrate and the cured product is 1.2 times or more the normal tensile bond strength. When methyl methacrylate polymer is used as component (B), the normal tensile bond strength and water-resistant tensile bond strength are as high as 1.0 N / mm 2 or higher.

[0241] Comparative Example 1:

[0242] Moisture-curable composition 7 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 10 parts by mass of a methyl (meth)acrylate polymer having no silyl group was used instead of the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0243] The normal tensile bond strength, water-resistant tensile bond strength and elongation of the moisture-curable composition 7 were 0.70 N / mm 2 , 0.70N / mm 2 and 110%, and did not meet the acceptable criteria. Moisture Curable Composition 7 was determined to be unacceptable.

[0244] Comparative Example 2:

[0245] Moisture-curable composition 8 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 10 parts by mass of a butyl acrylate polymer having a trimethoxysilyl group at the end was used instead of the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0246] The normal tensile bond strength, water-resistant tensile bond strength and elongation of the moisture curable composition 8 were 0.40 N / mm 2 , 0.50N / mm 2 and 140%, and did not meet the acceptable standard. Moisture Curable Composition 8 was determined to be unacceptable. It is believed that the water-resistant tensile adhesive strength was insufficient due to the use of an acrylate polymer whose main chain is not (meth)acrylic acid.

[0247] Comparative Example 3:

[0248] Moisture-curable composition 9 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 10 parts by mass of a 2-ethylhexyl acrylate polymer having carboxyl groups in the side chain and at the terminal was used instead of the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0249] The normal tensile adhesive strength, water-resistant tensile adhesive strength, tensile strength and elongation of the moisture-curable composition 9 were 0.40 N / mm 2 , 0.40N / mm 2 , 1.0N / mm 2 and 1,000%, and did not meet the acceptable criteria. Moisture Curable Composition 9 was determined to be unacceptable.

[0250] Comparative Example 4:

[0251] The moisture curable composition 10 was obtained using the same components, the same mass parts and the same preparation method as in Example 1, except that 10 mass parts of 2-ethylhexyl acrylate polymer having two hydroxyl groups at the terminals was used instead of the (meth)acrylate polymer (B). The same evaluation as in Example 1 was performed.

[0252] The normal tensile adhesive strength, tensile strength and elongation of the moisture curable composition 10 were 0.50 N / mm 2 , 1.1N / mm 2 and 200%, and did not meet the acceptable criteria. Moisture Curable Composition 10 was determined to be unacceptable.

[0253] Comparative Example 5:

[0254] Moisture-curable composition 11 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 1.0 parts by mass of 1,8-diazabicyclo[5.4.0]undec-7-ene available from FUJIFILM Wako Pure Chemical Corporation was used instead of the amine-based catalyst (C) and 22.5 parts by mass of polypropylene glycol (diol type, molecular weight: 400) available from FUJIFILM Wako Pure Chemical Corporation was used instead of the plasticizer (D). The same evaluation as in Example 1 was performed.

[0255] The normal tensile adhesive strength and water-resistant tensile adhesive strength of the moisture-curable composition 11 were each 0.30 N / mm 2 , and did not meet the acceptable criteria. Moisture Curable Composition 11 was determined to be unacceptable.

[0256] Comparative Example 6:

[0257] The moisture curable composition 12 was obtained by using the same components, the same mass parts and the same preparation method as in Example 1, except that 15.0 mass parts of GENIOSIL (registered trademark) STP-E 15 (viscosity at 25° C. was 10,000 mPas, represented by the formula: Y-[(CH2)3-SiR 1 a (OR 2 ) 3-a ] x represents, wherein Y is a divalent organic polymer group bonded via a urethane group containing an oxyalkylene group as a polymer chain, R 1 and R 2 is methyl, a is 0, and x is 2) in place of the silane-modified polymer (A). The same evaluation as in Example 1 was performed.

[0258] Moisture Curable Composition 12 did not cure and was therefore determined to be unacceptable. It is believed that adequate cure could not be achieved with an amine based catalyst because the crosslinkable silyl groups are in the gamma position of the polymer chain.

[0259] Comparative Example 7:

[0260] The moisture curable composition 13 was obtained by using the same components, the same mass parts and the same preparation method as in Example 1, except that 15.0 mass parts of GENIOSIL (registered trademark) STP-E 35 (viscosity at 25° C. is 30,000 mPas, represented by the formula: Y-[(CH2)3-SiR 1 a (OR 2 ) 3-a ] x represents, wherein Y is a divalent organic polymer group bonded via a urethane group containing an oxyalkylene group as a polymer chain, R 1 and R 2 is methyl, a is 0, and x is 2) in place of the silane-modified polymer (A). The same evaluation as in Example 1 was performed.

[0261] Moisture Curable Composition 13 did not cure and was therefore determined to be unacceptable. It is believed that adequate cure could not be achieved with the amine based catalyst because the crosslinkable silyl groups were in the gamma position of the polymer chain.

[0262] Comparative Example 8:

[0263] A moisture curable composition 14 was obtained using the same components, the same parts by mass, and the same preparation method as in Example 1, except that 25.0 parts by mass of GENIOSIL (registered trademark) STP-E 30 available from Wacker Chemie AG was used as the silane-modified polymer (A), no (meth)acrylate polymer (B) was used, 19.0 parts by mass of polypropylene glycol (diol type, molecular weight: 400) available from FUJIFILM Wako Pure Chemical Corporation was used as the plasticizer (D), and 2.0 parts by mass of GENIOSIL (registered trademark) GF 80 available from Wacker Chemie AG and 2.0 parts by mass of GENIOSIL (registered trademark) GF 69 were used as the adhesion promoter (F). The same evaluation as in Example 1 was performed.

[0264] GENIOSIL (registered trademark) GF 69 is tris[3-(trimethoxysilyl)propyl]isocyanurate.

[0265] The water-resistant tensile bond strength of moisture curable composition 14 was 0.49 N / mm 2 , does not meet the acceptable standard and is much less than the tensile bond strength of the normal state (0.73N / mm 2 ). Therefore, moisture curable composition 14 was determined to be unacceptable.

[0266] These evaluation results show that the moisture-curable composition containing the silane-modified polymer (A) represented by the above-mentioned general formula (1), the silyl group-containing (meth)acrylate polymer (B) and the amine-based catalyst having at least one alkoxy group has good rubber properties and good tensile adhesive strength even after immersion in water, although no metal catalyst is used.

[0267] As described above, when a (meth)acrylate polymer having a crosslinkable silyl group in the molecule is used as component (B), it is confirmed that the cured product obtained by curing the moisture curable composition of the present invention has a thermal conductivity of 0.75 N / mm 2 or greater normal tensile adhesive strength and a water-resistant tensile adhesive strength that is 1.0 or more times the normal tensile adhesive strength.

[0268] [Table 1]

[0269]

[0270] [Table 2]

[0271]

[0272] A part or all of the embodiments may be described as the following appendices, but are not limited to the following description. Each appendix may be combined with each note described in the claims.

[0273] Addendum 1:

[0274] A moisture curable composition comprising:

[0275] The silane-modified polymer (A) represented by the general formula (1):

[0276] Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0277] (wherein Y is an x-valent polymer group bonded via nitrogen, oxygen or sulfur,

[0278] R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups, R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group,

[0279] x is an integer from 1 to 10, and;

[0280] a is 0, 1, or 2);

[0281] a (meth)acrylate polymer (B) containing a crosslinkable silyl group in the molecule (ie, a (meth)acrylate polymer); and

[0282] An amine-based catalyst (C) having at least one alkoxy group.

[0283] Addendum 2:

[0284] A moisture curable composition according to Appendix 1, wherein:

[0285] The (meth)acrylate polymer (B) includes a (meth)acrylate monomer as a monomer unit constituting a main chain; and

[0286] The (meth)acrylate monomer is a monomer having an alkyl group having 1 to 5 carbon atoms ester-bonded to (meth)acrylic acid.

[0287] Addendum 3:

[0288] The moisture curable composition as described in Appendix 1 or 2, wherein the amine-based catalyst (C) is an aminosilane.

[0289] Addendum 4:

[0290] A moisture curable composition according to any one of Appendices 1 to 3, comprising,

[0291] Relative to 100 parts by mass of the moisture-curable composition as a whole,

[0292] 5 parts by mass or more and 90 parts by mass or less of the silane-modified polymer (A),

[0293] 5 parts by mass or more and 90 parts by mass or less of the (meth)acrylate polymer (B), and

[0294] 0.01 parts by mass or more and 10 parts by mass or less of the amine-based catalyst (C).

[0295] Addendum 5:

[0296] The moisture-curable composition according to any one of Appendixes 1 to 4, wherein the number average molecular weight of the silane-modified polymer (A) is 400 to 30,000, and -[(CH2)-SiR 1 a (OR 2 ) 3-a ] The number of groups is 1.5 or more and 2.2 or less.

[0297] Addendum 6:

[0298] A moisture curable composition according to any one of Appendices 1 to 5, comprising,

[0299] Relative to 100 parts by mass of the moisture-curable composition as a whole,

[0300] 5 parts by mass or more and 90 parts by mass or less of a silane-modified polymer (A),

[0301] 5 parts by mass or more and 90 parts by mass or less of a (meth)acrylate polymer (B),

[0302] 0.01 parts by mass or more and 10 parts by mass or less of an amine-based catalyst (C),

[0303] 0 parts by mass or more and 50 parts by mass or less of a plasticizer (D),

[0304] 0 parts by mass or more and 10 parts by mass or less of a dehydrating agent (E),

[0305] 0 parts by mass or more and 5 parts by mass or less of an adhesion promoter (F),

[0306] 0.1 parts by mass or more and 20 parts by mass or less of hydrophobized inorganic particles (G),

[0307] 0 parts by mass or more and 80 parts by mass or less of a filler (H), and

[0308] 0.01 parts by mass or more and 5 parts by mass or less of a stabilizer (I).

[0309] Addendum 7:

[0310] A method for improving water-resistant adhesion by bonding a substrate and a cured product obtained by curing a moisture curable composition, comprising:

[0311] The silane-modified polymer (A) represented by the general formula (1):

[0312] Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1)

[0313] (wherein Y has a polymer chain of polyoxyalkylene and is connected to -[CH2-SiR 1 a (OR 2 ) 3-a ] group bonded to a group,

[0314] R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups,

[0315] R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group,

[0316] R' is a monovalent optionally substituted hydrocarbon group bonded to SiC,

[0317] x is an integer from 1 to 10, and;

[0318] a is 0, 1, or 2);

[0319] a (meth)acrylate polymer (B) containing a crosslinkable silyl group in the molecule; and

[0320] an amine-based catalyst (C) having at least one alkoxy group,

[0321] Methods include:

[0322] A moisture-curable composition comprising component (B) is used, wherein component (B) is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule, so that after completing a water immersion test, the tensile adhesion strength between the substrate and the cured product reaches 1.0 times or more of that before the water immersion test, in which the substrate and the cured product are immersed in water at 23° C. for 168 hours.

[0323] Addendum 8:

[0324] An adhesive or sealing material comprising the moisture curable composition described in any one of Appendices 1 to 7.

[0325] Addendum 9:

[0326] A laminate comprising: a substrate; and a cured product obtained by curing the moisture curable composition described in any one of Appendices 1 to 7.

Claims

1. A moisture curable composition comprising: The silane-modified polymer (A) represented by the general formula (1): Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1) (wherein Y is an x-valent polymer group bonded via nitrogen, oxygen or sulfur, R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups, R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group, x is an integer from 1 to 10, and; a is 0, 1, or 2); a (meth)acrylate polymer (B) containing a crosslinkable silyl group in the molecule; and An amine-based catalyst (C) having at least one alkoxy group.

2. The moisture curable composition according to claim 1, wherein: The (meth)acrylate polymer (B) includes a (meth)acrylate monomer as a monomer unit constituting a main chain thereof; and The (meth)acrylate monomer is a monomer having an alkyl group having 1 to 5 carbon atoms ester-bonded to (meth)acrylic acid.

3. The moisture curable composition according to claim 1 or 2, wherein the amine-based catalyst (C) is an aminosilane.

4. The moisture curable composition according to claim 1 or 2, comprising: Relative to 100 parts by mass of the moisture-curable composition as a whole, 5 parts by mass or more and 90 parts by mass or less of the silane-modified polymer (A), 5 parts by mass or more and 90 parts by mass or less of the (meth)acrylate polymer (B), and 0.01 parts by mass or more and 10 parts by mass or less of the amine-based catalyst (C).

5. The moisture-curable composition according to claim 1, wherein the silane-modified polymer (A) has a number average molecular weight of 400 to 30,000, and -[(CH2)-SiR 1 a (OR 2 ) 3-a ] The number of groups is 1.5 or more and 2.2 or less.

6. The moisture curable composition according to claim 4, comprising: Relative to 100 parts by mass of the moisture-curable composition as a whole, 5 parts by mass or more and 90 parts by mass or less of the silane-modified polymer (A), 5 parts by mass or more and 90 parts by mass or less of the (meth)acrylate polymer (B), 0.01 parts by mass or more and 10 parts by mass or less of the amine-based catalyst (C), 0 parts by mass or more and 50 parts by mass or less of a plasticizer (D), 0 parts by mass or more and 10 parts by mass or less of a dehydrating agent (E), 0 parts by mass or more and 5 parts by mass or less of an adhesion promoter (F), 0.1 parts by mass or more and 20 parts by mass or less of hydrophobized inorganic particles (G), 0 parts by mass or more and 80 parts by mass or less of a filler (H), and 0.01 parts by mass or more and 5 parts by mass or less of a stabilizer (I).

7. A method for improving water-resistant adhesion by bonding a substrate to a cured product obtained by curing a moisture curable composition, the method comprising: The silane-modified polymer (A) represented by the general formula (1): Y-[CH2-SiR 1 a (OR 2 ) 3-a ] x (1) (wherein Y has a polymer chain which is a polyoxyalkylene and is bonded to -[CH2-SiR 1 a (OR 2 ) 3-a ] group, R 1 may be the same as or different from each other and are monovalent optionally substituted SiC-bonded hydrocarbon groups, R 2 may be the same as or different from each other and are a hydrogen atom or a monovalent optionally substituted hydrocarbon group, R' is a monovalent optionally substituted hydrocarbon group bonded to SiC, x is an integer from 1 to 10, and; a is 0, 1, or 2); a (meth)acrylate polymer (B) containing a crosslinkable silyl group in the molecule; and an amine-based catalyst (C) having at least one alkoxy group, The method comprises: A moisture-curable composition comprising component (B) is used, wherein component (B) is a (meth)acrylate polymer containing a crosslinkable silyl group in the molecule, so that after a water immersion test is performed, the tensile adhesive strength between the substrate and the cured product reaches 1.0 times or more of that before the water immersion test is performed, in which the substrate and the cured product are immersed in water at 23° C. for 168 hours.

8. An adhesive or sealing material comprising the moisture curable composition according to claim 1. 9 . A laminate comprising: a substrate; and a cured product obtained by curing the moisture curable composition according to claim 1 .

Citation Information

Patent Citations

  • Process for the preparation of organyloxysilylterminated polymers

    EP1535940B1

  • Continuous polymer-analogous reaction of reactive silane monomers with functionalised polymers

    EP1896523B1

  • Moisture-curing compositions containing silane-functional polymers and aminosilane adducts with good adhesive properties

    WO2007085622A1